Variable responses on early development of shallot (Allium ascalonicum) and mustard (Brassica juncea) plants to Bacillus cereus inoculation - Ab. Aziz, Zakry Fitri; Mohd Saud, Halimi; Abdul Rahim, Khairuddin; Ahmed, Osumanu Haruna (Malaysian Society for Microbiology, 2012)
Aim: Auxin, a phytohormone secreted by plant growth-promoting rhizobacteria is one of the direct mechanisms vital for plant growth promotion. A laboratory experiment was conducted to observe the effect of IAA-producing and non-IAA-producing diazotroph Bacillus cereus strains on early growth of shallot (Allium ascalonicum) and mustard (Brassica juncea) plants. Methodology and Results: Treatments evaluated were as follows: Control = uninoculated, no inoculation, UPMLH1 = IAA-producing B. cereus UPMLH1, and UPMLH24 = non-IAA-producing B. cereus UPMLH24. Inoculation with IAA-producing B. cereus UPMLH1 significantly increased shallot adventitious roots (root number and length) and shoot growth (19 to 54% increment). Inoculation of non-IAA-producing B. cereus UPMLH24 did not significantly improve growth of adventitious roots of shallot as compared to uninoculated control, except its shoot (up to 40% increase). However, primary roots and shoot growth of mustard plants significantly increased through inoculation with IAA-producing and non-IAA-producing strains (14 to 73% increment). Conclusion, Significance and Impact of Study: The results indicated that exogenous IAA secreted by B. cereus UPMLH1 might have play an important role in inducing roots of shallot bulbs and it may have a variable promotional effect depending on plant species.